Prone positioning for patients intubated for severe acute respiratory distress syndrome (ARDS) secondary to COVID-19: a retrospective observational cohort study. (January 2021) - Weiss, Tyler T.; Cerda, Flor; Scott, J. Brady; Kaur, Ramandeep; Sungurlu, Sarah; Mirza, Sara H.; Alolaiwat, Amnah A.; Kaur, Ramandeep; Augustynovich, Ashley E.; Li, Jie
Abstract: Background: The role of repeated prone positioning in intubated subjects with acute respiratory distress syndrome caused by COVID-19 remains unclear. Methods: We conducted a retrospective observational cohort study of critically ill intubated patients with COVID-19 who were placed in the prone position between March 18, 2020 and March 31, 2020. Exclusion criteria were pregnancy, reintubation, and previous prone positioning at a referring hospital. Patients were followed up until hospital discharge. The primary outcome was oxygenation assessed by partial pressure of oxygen/fraction of inspired oxygen ratio ( P ao 2 /Fio 2 ) ratio. A positive response to proning was defined as an increase in P ao 2 /Fio 2 ratio ≥20%. Treatment failure of prone positioning was defined as death or requirement for extracorporeal membrane oxygenation (ECMO). Results: Forty-two subjects (29 males; age: 59 [52–69] yr) were eligible for analysis. Nine subjects were placed in the prone position only once, with 25 requiring prone positioning on three or more occasions. A total of 31/42 (74%) subjects survived to discharge, with five requiring ECMO; 11/42 (26%) subjects died. After the first prone positioning session, Pao 2 /Fio 2 (mean (standard deviation)) ratio increased from 17.9 kPa (7.2) to 28.2 kPa (12.2) ( P <0.01). After the initial prone positioning session, subjects who were discharged from hospital were more likely to have an improvement in Pao 2 /Fio 2 ratio ≥20%, compared with those requiring ECMO or who died. Conclusion: Patients with COVID-19 acute respiratory distress syndrome frequently responded to initial prone positioning with improved oxygenation. Subsequent prone positioning in subjects discharged from hospital was associated with greater improvements in oxygenation.